Indonesian Liberal Thought Outlook Towards Sharia’s Law - Al- Salam, Radwan Nour (Journal of Islamic Sciences, 2019)
This study focuses on the attitude of the Indonesian liberal thought towards sharia laws and discussion about their objection on them. this study used the critical inductive method to the intellectual thinking of liberal’s prominent figures in Indonesia. The study has reached the important results: • The Indonesian liberal discourse stands on the issues of the stability of the sharia and its comprehensive position. • Indonesian liberalists thought to reject sharia arbitration due to its contradiction to the principles of liberal thought and its foundations, such as individual freedom, democracy, and secularism. • Indonesian liberalists thought tried to provide the new version of jurisprudence: the most prominent of new provisions were proposed: It is permissible to stand in ’Arafah besides the ninth day of Dhu’l- Hijjah.